Can Ethical Leadership Improve Employees’ Well-Being at Work? Another Side of Ethical Leadership Based on Organizational Citizenship Anxiety - Fu, Jingtao; Long, Yijing; He, Qi; Liu, Yazhen (Frontiers in Psychology, 2020)
Most of the previous literature has focused on the positive effects of ethical leadership on organizations and employees, but some studies have unexpectedly found that ethical leadership is negatively related to employees' well-being at work. Based on the theory of workplace anxiety, this research explored whether ethical leadership can reduce employees' well-being at work by causing them to feel anxious about organizational citizenship behavior and whether organizational concern motivation moderates this mechanism. We collected 227 three-stage time-crossed data samples from 12 institutions in Hainan China, then tested our research hypotheses to confirm that ethical leadership has a negative impact on employees' well-being at work under certain conditions. We found that: (1) ethical leadership is significantly and positively correlated with the organizational citizenship anxiety perceived by employees, (2) organizational citizenship anxiety perceived by employees plays a completely mediating role between ethical leadership and employee well-being at work, and (3) organizational concern motivation not only negatively moderates the negative correlation between employees’ organizational citizenship anxiety and well-being at work, but also further moderates the indirect negative effect of ethical leadership on employee well-being at work through organizational citizenship anxiety.